Base‐Catalyzed Hydration of Silicon‐Containing Activated Alkynes: The Effect of Substituents at the Triple Bond. Issue 34 (10th September 2020) - Mareev, Alexander V.; Andreev, Mikhail V.; Ushakov, Igor A.
Abstract: Metal‐catalyzed hydration of alkynes is rapidly developing research direction in organic synthesis. However, base‐catalyzed hydration of activated acetylenes remains much less studied. In contrast to the metal‐catalyzed reactions leading to carbonyl compounds, base‐catalyzed hydration gives vinyl ethers of different structure or cyclic products depending on the nature of substituents. So, it is found that 1, 4‐diazabicyclo [2.2.2]octane (DABCO)‐catalyzed hydration of trimethylsilylated electron‐deficient alkynes of general formula Me3 SiC≡CCOX (X=Ph, NR 1 R 2, OEt) proceeds at room temperature to afford push‐pull divinyl ethers in 56–94 % yields, while 4‐trimethylsilyl‐3‐butyne‐2‐one (X=Me) reacts non‐selectively delivering both symmetrical and unsymmetrical divinyl ethers (dimerization products). Contrary to ketones, amides and esters, 3‐trimethylsilylpropynal gives under the same conditions 4 H ‐pyran, as we shown earlier. Abstract : The base‐catalyzed hydration of the silylated electron‐deficient alkynes has been studied. It is found that the direction and efficiency of the reaction is very sensitive toward the substituents nature. The hydration of acetylenic amides and ester leads to push‐pull divinyl ethers. In case of the ketones, the reaction outcome depends on the process conditions and reactants structure. Both symmetrical and unsymmetrical divinyl ethers are synthesized. Early it has been shown that the hydration of aldehydes gives 4 H ‐pyran.